Effect of ration supplemented with zinc on some hematological parameters in angora goats - Nurcan Dönmez; Ercan Keskin (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine the effects of zinc supplementation on some haematological parameters in Angora goats. In the study, 10-12 months aged and 12 Angora goals weighing 15-22 kg were used. Group 1(Conlrol) and group 2(Experimental) were fed with a standart ration containing 35 ppm Zn and the same ration supplemented with 250 ppm Zn respectively as ad libitum for 6 months. In the study, while the plasma zinc levels of control and experimental groups were 0.54-0.64 and 0.73-1.13 µg/ml, the plasma zinc levels of experimental group were signiliciantly(p<0.05) higher, except first sampling time, than in the control group. Although the erythrocyte count, haemoglobine amount and haematocrit levels in the group supplemented with zinc were generally found to be higher than those in control group, the difference at 3rd month was important alone(p<0.05). It was observed that the erythrocyte count, haemoglobin amount and haematocrit levels in control group tended to decrease as compared with the first month values of the same group. The total protein levels in experimental group were found to bo generally higher, unless important, than those in control group. Although the albumin levels in experimental group were obviously higher as compared with that of control group, the difference of 5. month lonely was statistically important (p<0.05). In Ihe study there was no difference between groups in respect of total leucocyte count and lymphocyte percentage in any time, but it was striking that these parameters were higher in the group supplemented with zinc when compared with control group in all sampling times. In addition to, both T and B lymphocyte percentages also were close each other in either groups during all the study. Consequently, these data obtained in Angora goats which of the ration supplemented with zinc, may have been considered to be beneficial in point of exhibiting the effects of zinc on at least these parameters.